Posttransplant maintenance therapy for acute leukemias. Issue 2 (March 2019) - Poudel, Shyam K.; de Lima, Marcos; Metheny, Leland
Abstract : Purpose of review: Allogeneic hematopoietic stem cell transplantation cures a significant proportion of patients with hematological malignancies. Unfortunately, leukemia recurrence is the main cause of transplant failure. Risk factors for relapse include presence of minimal residual disease and a variety of well-recognized leukemia prognostic factors. Posttransplant therapy could decrease the risk of leukemia relapse and is under investigation. In this review, we summarize the current research in maintenance therapy for the prevention of acute leukemia recurrence after allogeneic transplant. Recent findings: Epigenetic modifiers, tyrosine kinase inhibitors, and antibody–drug conjugates are among potential maintenance therapies given their side-effect profile and many are currently under investigation. In the posttransplant setting, the phase I/II data are maturing and have been encouraging enough to lead to the initiation of multicenter phase III randomized clinical trials. Summary: Currently, there is no standard of care for posttransplant maintenance for acute leukemias. Further investigation into the efficacy and safety of posttransplant maintenance is warranted given phase I/II clinical trials results. Beyond chemo-immunotherapy, the use of targeted cellular therapy, such as chimeric antigen receptor T cells, is a potential therapy as well.